Suffering “Like This”: Interpretation and the Pedagogical Disruption of the Dual System of Education - Gilham, Christopher M. (Paideusis)

(untitled) (Canadian Philosophy of Education Society, 2014)
In this paper I attempt to show how my graduate work in interpretive studies transformed my previous work as a special education consultant. Using Hans-Georg Gadamer's hermeneutics, as well as Ivan Illich's notions of iatrogenesis and counter-productivity, I discuss my work with a school team as they struggled throughout a school year with a special education classroom for students with diagnosed mental health disorders.